Amino acids and the brain: Do they play a role in "central fatigue"? - Meeusen, R.; Watson, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
It is clear that the cause of fatigue is complex, influenced by both events occurring in the periphery and the central nervous system (CNS). It has been suggested that exercise-induced changes in serotonin (5-HT), dopamine (DA), and noradrenaline (NA) concentrations contribute to the onset of fatigue during prolonged exercise. Serotonin has been linked to fatigue because of its documented role in sleep, feelings of lethargy and drowsiness, and loss of motivation, whereas increased DA and NA neurotransmission favors feelings of motivation, arousal, and reward. 5-HT has been shown to increase during acute exercise in running rats and to remain high at the point of fatigue. DA release is also elevated during exercise but appears to fall at exhaustion, a response that may be important in the fatigue process. The rates of 5-HT and DA/NA synthesis largely depend on the peripheral availability of the amino acids tryptophan (TRP) and tyrosine (TYR), with increased brain delivery increasing serotonergic and DA/NA activity, respectively. TRP, TYR, and the branched-chained amino acids (BCAAs) use the same transporter to pass through the blood-brain barrier, meaning that the plasma concentration ratio of these amino acids is thought to be a very important marker of neurotransmitter synthesis. Pharmacological manipulation of these neurotransmitter systems has provided support for an important role of the CNS in the development of fatigue. Work conducted over the last 20 y has focused on the possibility that manipulation of neurotransmitter precursors may delay the onset of fatigue. Although there is evidence that BCAA (to limit 5-HT synthesis) and TYR (to elevate brain DA/NA) ingestion can influence perceived exertion and some measures of mental performance, the results of several apparently well-controlled laboratory studies have yet to demonstrate a clear positive effect on exercise capacity or performance. There is good evidence that brain neurotransmitters can play a role in the development of fatigue during prolonged exercise, but nutritional manipulation of these systems through the provision of amino acids has proven largely unsuccessful.